A Study of Depression among Unemployed Graduates in the context of Sexuality - Dave, Trushaben Kiritkumar; Dodiya, Malabhai B. (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The main objective of the present study was to study the depression of unemployed graduates in terms of sexuality. A total of 300 unemployed graduates were selected as the sample through random sampling method. Out of which 150 were young men and 150 were young women. Data were collected through Chudasama S. D. (2018) Depression Scale Test. Based on the scores obtained, the data was analyzed through t-test. At the end of the study, it was found that there was a significant difference between the mean scores of depressions in terms of sexuality among unemployed graduates, that is, depression was more observed in young women than in young men.